Physicochemical parameters data assimilation for efficient improvement of water quality index prediction: Comparative assessment of a noise suppression hybridization approach - Rezaie-Balf M.; Attar N.F.; Mohammadzadeh A.; Murti M.A.; Ahmed A.N.; Fai C.M.; Nabipour N.; Alaghmand S.; El-Shafie A. (Elsevier Ltd, 2023)
Forecasting; Kalman filters; Mean square error; Neural networks; Quality assurance; Water conservation; Water management; Water quality; Water supply; Comparative assessment; Data assimilation methods; Ensemble Kalman Filter; Hydrological variables; Intrinsic time-scale decompositions; Physicochemical parameters; Preprocessing techniques; Root mean square errors; River pollution